Activating Single‐Atom Ni Site via First‐Shell Si Modulation Boosts Oxygen Reduction Reaction. Issue 8 (11th December 2022) - Wang, Fangqing; Li, Ying; Zhang, Rui; Liu, Hui; Zhang, Yangyang; Zheng, Xuerong; Zhang, Jun; Chen, Cong; Zheng, Shijian; Xin, Huolin L.
Abstract: Atomically dispersed nitrogen‐coordinated 3d transition‐metal site on carbon support (M‐NC) are promising alternatives to Pt group metal‐based catalysts toward oxygen reduction reaction (ORR). However, despite the excellent activities of most of M‐NC catalysts, such as Fe‐NC, Co‐NC et al., their durability is far from satisfactory due to Fenton reaction. Herein, this work reports a novel Si‐doped Ni‐NC catalyst (Ni‐SiNC) that possesses high activity and excellent stability. X‐ray absorption fine structure and aberration‐corrected transmission electron microscopy uncover that the single‐atom Ni site is coordinated with one Si atom and three N atoms, constructing Ni‐Si1 N3 moiety. The Ni‐SiNC catalyst exhibits a half‐wave potential (E1/2 ) of 0.866 V versus RHE, with a distinguished long‐term durability in alkaline media of only 10 mV negative shift in E1/2 after 35 000 cycles, which is also validated in Zn‐air battery. Density functional theory calculations reveal that the Ni‐Si1 N3 moiety facilitates ORR kinetics through optimizing the adsorption of intermediates. Abstract : Due to the rational structure of the active centres and the Fenton reaction‐free nature, the synthesized Ni‐SiNC catalyst exhibits excellent ORR activity and long‐term stability. The introduction of Si increases the charge density of the single‐atom Ni centres and optimizes the adsorption energy of the ORR intermediates on the Ni‐Si1 N3 sites.